PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK AMPLANG KELOMPOK UKM â€œWANITA MANDIRI SALIKIâ€ DI DESA SALIKI - Irwansyah; Ilham; Hendra (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2022)
The aim of this thesis is to determine the partial and simultaneous influence of product quality, price and brand image variables on purchasing decision variables for the SME amplang product